A surface modification method of a sodium-ion battery negative electrode hard carbon material
Patent Information
- Application Number
- CN202611375702.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0012]本发明的目的在于提供一种钠离子电池负极硬碳材料表面改性方法,以解决上述背景技术中提出的现有技术中硬碳材料表面改性方法存在的改性效果不均衡、长期界面稳定性不足、工艺复杂且可能引入副作用的问题
1、本发明中, 通过设置液相浸渍沉积与可控低温热处理相结合的工艺,使得碳源或聚合物前驱体能够以溶液形式均匀包裹于硬碳基体表面,并在中低温下原位转化为一层厚度可控、结构致密且与基体结合牢固的有机-无机复合改性层,从而实现了对硬碳材料表面活性位点的有效、均匀钝化,显著减少了首次充放电过程中电解液的不可逆分解,进而大幅提升了钠离子电池的首圈库伦效率。
Smart Images

Figure CN122907634A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery materials technology, and more specifically, to a method for surface modification of hard carbon materials for sodium-ion battery anodes. Background Technology
[0002] Sodium-ion batteries are rechargeable batteries that primarily function by the movement of sodium ions between the positive and negative electrodes, similar in principle to lithium-ion batteries. As an important supplement and alternative to lithium-ion batteries, sodium-ion batteries have attracted widespread attention due to the abundance and low cost of sodium resources. Among various anode materials, hard carbon materials are considered one of the most commercially promising anode materials for sodium-ion batteries due to their suitable sodium storage platform, high specific capacity, and wide availability.
[0003] However, hard carbon materials still face some key challenges in practical applications, which restrict the further improvement of their electrochemical performance and industrial application. These challenges mainly stem from their intrinsic surface characteristics: First, hard carbon materials have a large initial specific surface area and abundant defects and oxygen-containing functional groups on their surface. This leads to a violent and irreversible decomposition reaction of the electrolyte on its surface during the first charge and discharge process, forming an excessively thick and unstable solid electrolyte interfacial film. This results in the irreversible consumption of a large amount of sodium ions and electrolyte, leading to a low coulombic efficiency in the first cycle of the battery. Second, the interfacial compatibility between hard carbon and the electrolyte is poor. During long-term cycling, especially under high current or extreme temperature conditions, interfacial side reactions continue to occur, and the SEI film repeatedly breaks down and reconstructs. This not only continuously consumes active sodium ions and electrolyte but also leads to the gradual deterioration of the electrode structure, seriously affecting the cycle stability and rate performance of the battery.
[0004] To overcome the above problems, various surface modification studies have been conducted on hard carbon materials in the prior art, mainly including: Surface coating modification: For example, amorphous carbon layers, metal oxides, or conductive polymer coatings are introduced onto hard carbon surfaces using methods such as organic pyrolysis, atomic layer deposition, or chemical vapor deposition. However, these methods often face the challenge of controlling the uniformity of the coating layer. An excessively thick coating layer can hinder sodium ion diffusion and increase internal resistance; while an excessively thin or uneven coating layer cannot provide effective physical isolation and protection. Furthermore, some coating processes (such as high-temperature vapor deposition) are complex and costly, or the coating precursors used are environmentally unfriendly.
[0005] Surface element doping / functional group modulation: Introducing heteroatoms such as nitrogen, sulfur, and phosphorus into hard carbon surfaces via gas-phase, liquid-phase, or solid-phase methods aims to improve surface wettability and electronic conductivity. However, this method often struggles to precisely control the type, content, and distribution of dopants, potentially leading to excessive surface structural disorder, introducing new irreversible reaction sites, and possibly exacerbating side reactions or causing a further decrease in initial efficiency. Furthermore, heteroatoms may pose a risk of dissolution during cycling, affecting long-term interfacial stability.
[0006] Surface etching or structural reconstruction: Hard carbon surfaces are etched using strong acids, strong alkalis, or high-temperature oxidation to control porosity and surface state. While this method can partially improve ion transport, it is highly prone to causing surface structural damage, generating more defects, accelerating electrolyte decomposition, and easily introducing impurities, posing challenges to the environmental friendliness and consistency of the process.
[0007] In summary, the main problems and defects in existing surface modification technologies for hard carbon materials are as follows: (1) Insufficient balance and controllability of modification effect: It is difficult to achieve an ideal balance between effectively passivating highly active surfaces, reducing irreversible consumption (improving first efficiency) and maintaining fast ion / electron transport channels (ensuring rate performance); the thickness, uniformity and structure of the modified layer are difficult to precisely control.
[0008] (2) Limited improvement in long-term interface stability: Many modification methods have failed to construct a stable SEI film with high mechanical strength, good elasticity and low diffusion barrier. During long-term cycling, the continuous occurrence of interface side reactions cannot be effectively suppressed, and the cycle life, especially the stability under harsh conditions, still needs to be improved.
[0009] (3) Process complexity and cost issues: Some modification methods involve multi-step reactions, harsh conditions (such as ultra-high vacuum, extremely high temperature) or expensive raw materials, which are complex and energy-intensive, and are not conducive to large-scale industrial production.
[0010] (4) May introduce new side effects: such as kinetic deterioration caused by non-uniform coating, additional defects and side reactions caused by overdoping or etching.
[0011] Therefore, developing a surface modification method that is relatively simple in process, cost-controllable, and can simultaneously and effectively improve the first-cycle coulombic efficiency, rate performance, and long-cycle stability of hard carbon anodes is of great significance for promoting the practical application of sodium-ion batteries. Summary of the Invention
[0012] The purpose of this invention is to provide a method for surface modification of hard carbon materials for sodium-ion battery anodes, in order to solve the problems of uneven modification effect, insufficient long-term interface stability, complex process and possible introduction of side effects in the existing hard carbon material surface modification methods mentioned in the background art.
[0013] To achieve the above objectives, the present invention aims to provide a method for surface modification of hard carbon materials for sodium-ion battery anodes, comprising the following steps: S1. Pretreatment: The hard carbon raw material is pretreated to obtain a clean hard carbon matrix; S2. Preparation of precursor solution: Prepare a coated precursor solution containing a carbon source or polymer source and a catalyst. S3. Impregnation and deposition: The clean hard carbon matrix obtained in step S1 is dispersed in the coating precursor solution prepared in step S2, and liquid phase impregnation and deposition are performed to make the precursor uniformly adhere to the surface of the hard carbon matrix. S4. Separation and drying: The hard carbon matrix with the precursor attached to its surface obtained in step S3 is separated and dried to obtain a hard carbon intermediate coated with the precursor. S5. Low-temperature heat treatment: Under a protective atmosphere, the hard carbon intermediate coated with the precursor obtained in step S4 is subjected to low-temperature heat treatment at a temperature of [temperature value missing]. ,in The heat treatment time is ,in This causes the precursors attached to the surface to crosslink, solidify, or partially carbonize, forming a uniform, dense, and firmly bonded organic-inorganic composite modified layer on the surface of the hard carbon matrix. S6. Cooling: The hard carbon matrix after heat treatment in step S5 is naturally cooled to 20℃-30℃ to obtain the surface-modified hard carbon material. S7. Post-processing: The surface-modified hard carbon material obtained in step S6 is post-processed, including grinding and sieving, to obtain the final product.
[0014] As a further improvement to this technical solution, the specific preprocessing steps in step S1 are as follows: S11. Pickling treatment: Immerse the hard carbon raw material in an acidic solution at a temperature... Lower stirring processing time To remove surface impurities and some unstable oxygen-containing functional groups, among which , ; S12. Washing treatment: The acid-washed hard carbon raw material is repeatedly washed with deionized water until the pH value of the washing solution reaches 6-8. S13. Drying treatment: Place the washed hard carbon raw material in a dry environment at a temperature... Next drying time A clean hard carbon matrix is obtained, in which... , .
[0015] As a further improvement to this technical solution, the specific steps for preparing the precursor solution in step S2 are as follows: S21. Raw material selection and weighing: Select a carbon source or polymer source. and catalysts And weigh them precisely; S22, Solvent Dissolution: Dissolve the weighed carbon source or polymer source in solvent. and catalysts Add solvent middle; S23. Stirring and homogenizing: at temperature Continue stirring time The process continues until the solute is completely dissolved and a homogeneous and stable solution is formed, thus obtaining the coated precursor solution. , .
[0016] As a further improvement to this technical solution, the carbon source or polymer source is selected from at least one of glucose, sucrose, phenolic resin, polyvinyl alcohol, polypyrrole, and polyaniline; the catalyst is an acidic catalyst or a metal salt catalyst; and the solvent... The solvent is water, ethanol, acetone, or a mixture thereof, and the coating precursor solution contains a carbon source or a polymer source. mass concentration is ,catalyst mass concentration is And satisfy , %.
[0017] As a further improvement to this technical solution, the specific operation steps for impregnation deposition in step S3 are as follows: S31. Dispersion and mixing: The clean hard carbon matrix obtained in step S1 is added to the coating precursor solution prepared in step S2, and mechanical stirring or ultrasonic dispersion is performed to form a uniform suspension system. S32. Constant Temperature Impregnation: The suspension system is placed in a constant temperature environment, and impregnation is performed at a constant temperature. Subsequent immersion time And ensure that the hard carbon matrix is in full contact with the precursor solution, wherein , ; S33. Deposition complete: After impregnation, the precursor is uniformly attached to the surface of the hard carbon matrix through physical adsorption and / or chemical action, resulting in a hard carbon matrix with the precursor attached to its surface.
[0018] As a further improvement to this technical solution, the mass ratio of the hard carbon matrix to the solute in the coated precursor solution in step S33 is... satisfy The solute in the coated precursor solution is a carbon source or a polymer source and a catalyst.
[0019] As a further improvement to this technical solution, the specific operation steps for separation and drying in step S4 are as follows: S41. Solid-liquid separation: The hard carbon matrix with the precursor attached to its surface obtained in step S33 is separated from the remaining coated precursor solution. The separation method is filtration or centrifugation. S42. Cleaning and Pre-drying: Use a small amount of the solvent described above. The separated solid material is rinsed to remove excess solute physically adsorbed on the surface, followed by temperature... The following steps are performed to initially dry the residue and remove any residual solvent. ; S43. Deep Drying: Place the pre-dried solid material in a drying oven under vacuum or inert atmosphere protection, and dry it at a temperature... Deep drying time A thoroughly dried hard carbon intermediate with uniform precursor coating was obtained, wherein... , .
[0020] As a further improvement to this technical solution, the specific operation steps for the low-temperature heat treatment in step S5 are as follows: S51. Atmosphere protection and charging: The hard carbon intermediate with uniform precursor coating obtained in step S43 is placed in a heat treatment furnace, and a protective atmosphere is introduced into the furnace. The protective atmosphere is nitrogen, argon or a mixture thereof. S52, Continuous heating: at the set heating rate The temperature inside the heat treatment furnace is raised from room temperature to the target heat treatment temperature. The heating rate satisfy The target heat treatment temperature satisfy ; S53, Isothermal Reaction: The reaction proceeds at the target heat treatment temperature. Then, maintain this temperature for a constant heating time. ,in This causes the precursors attached to the surface of the hard carbon intermediate to undergo cross-linking, curing, or partial carbonization reactions, thereby forming the organic-inorganic composite modified layer on the surface of the hard carbon matrix.
[0021] As a further improvement to this technical solution, the specific steps for cooling down in step S6 are as follows: S61. Cooling with the furnace: After completing the constant temperature heat treatment in step S53, stop heating and allow the heat treatment furnace to cool down naturally under the continuous protection of the protective atmosphere. S62. Controlled-rate cooling: Controlling the cooling rate so that the furnace temperature drops from the target heat treatment temperature at a rate not exceeding 10℃ / min. Temperatures dropped below 100°C; S63. Remove the material: After the temperature inside the furnace has cooled naturally to 20℃-30℃, turn off the protective atmosphere and remove the heat-treated hard carbon material to obtain the surface-modified hard carbon material.
[0022] As a further improvement to this technical solution, the specific post-processing steps in step S7 are as follows: S71. Preliminary grinding: The surface-modified hard carbon material taken out in step S63 is preliminarily crushed or ground to break up any possible agglomerates. S72. Fine sieving: The ground material is sieved and classified using a standard sieve to select powder that meets the target particle size range. The mesh size of the standard sieve is between 300 and 500 mesh. S73. Packaging and Storage: The sieved final product is packaged and stored in a dry, sealed container for use in the preparation of sodium-ion battery anodes.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, by setting up a process that combines liquid phase immersion deposition with controllable low-temperature heat treatment, the carbon source or polymer precursor can be uniformly coated on the surface of the hard carbon matrix in solution form, and then transformed in situ at medium and low temperatures into an organic-inorganic composite modified layer with controllable thickness, dense structure and strong bonding with the matrix. This achieves effective and uniform passivation of the active sites on the surface of the hard carbon material, significantly reduces the irreversible decomposition of the electrolyte during the first charge and discharge process, and thus greatly improves the first-cycle coulombic efficiency of the sodium-ion battery.
[0024] 2. In this invention, by setting an organic-inorganic composite modified layer that has moderate conductivity, good mechanical strength and elasticity, the layer can act as a stable physical barrier and an optimized ion transport interface during battery cycling, thereby effectively suppressing the repeated rupture and reconstruction of the solid electrolyte interface film, reducing the continuous consumption of active sodium and electrolyte, and thus significantly enhancing the cycling stability and lifespan of the hard carbon anode under long-term cycling, especially under high-rate and wide-temperature conditions.
[0025] 3. In this invention, by setting up an overall process route with liquid phase method and medium and low temperature heat treatment as the core, the entire modification process does not need to rely on complex and expensive equipment such as atomic layer deposition and chemical vapor deposition, thereby greatly reducing process complexity, equipment investment and energy consumption, effectively controlling production costs, and thus greatly improving the feasibility and economy of industrial production of this surface modification method.
[0026] 4. In this invention, by setting precisely controlled precursor concentration, impregnation time, heat treatment temperature and time, and mild reaction conditions, the modification process can precisely control the thickness and properties of the surface modification layer without damaging the hard carbon bulk structure. This avoids additional defects, kinetic obstacles, or new side reaction sites introduced by over-coating, vigorous doping, or strong etching. As a result, while improving the first-time efficiency and stability, it ensures good rate performance of the material and achieves synergistic optimization of comprehensive electrochemical performance. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the surface modification method for the hard carbon material of the sodium-ion battery negative electrode according to the present invention. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In one specific embodiment, such as Figure 1 As shown, this invention provides a method for surface modification of hard carbon materials for sodium-ion battery anodes. By combining liquid-phase impregnation deposition with controlled low-temperature heat treatment, a uniform, dense, stable, and firmly bonded organic-inorganic composite modified layer is constructed on the surface of the hard carbon matrix. This layer simultaneously optimizes the interface, stabilizes the SEI (Sediment-Insulation Interphase), and promotes mass transfer. The method specifically includes the following steps: Step 1: Pretreatment: The hard carbon raw material is pretreated to obtain a clean hard carbon matrix.
[0030] Step 2: Prepare the precursor solution: Prepare a coated precursor solution containing a carbon source or polymer source and a catalyst.
[0031] Step 3, Impregnation and Deposition: The clean hard carbon matrix obtained in the above steps is dispersed in the coating precursor solution prepared in the above steps, and liquid phase impregnation and deposition are performed to make the precursor uniformly adhere to the surface of the hard carbon matrix.
[0032] Step 4: Separation and drying: The hard carbon matrix with the precursor attached to its surface obtained in the above steps is separated and dried to obtain the hard carbon intermediate coated with the precursor.
[0033] Step 5: Low-temperature heat treatment: Under a protective atmosphere, the hard carbon intermediate coated with the precursor obtained in the above steps is subjected to low-temperature heat treatment at a temperature of [temperature value missing]. ,in The heat treatment time is ,in This causes the precursors attached to the surface to crosslink, solidify, or partially carbonize, forming a uniform, dense, and firmly bonded organic-inorganic composite modified layer on the surface of the hard carbon matrix.
[0034] Step 6: Cooling: Allow the heat-treated hard carbon matrix to cool naturally to 20℃-30℃ to obtain the surface-modified hard carbon material.
[0035] Step 7: Post-processing: The surface-modified hard carbon material obtained in the above steps is post-processed, including grinding and sieving, to obtain the final product.
[0036] Example 1: Step 1, Pretreatment: Place 5g of commercial hard carbon powder in a 1M dilute hydrochloric acid solution, stir and acid wash at 60℃ for 2 hours, then wash repeatedly with deionized water until the filtrate is neutral, and finally dry in a vacuum drying oven at 120℃ for 12 hours to obtain a clean hard carbon matrix.
[0037] Step 2: Prepare the coating precursor solution: Weigh 0.5g of glucose (carbon source) and 0.05g of phosphoric acid (catalyst), dissolve them in 50g of deionized water, and stir magnetically until completely dissolved to obtain homogeneous solutions with mass concentrations of 1wt% and 0.1wt%, respectively.
[0038] Step 3, Liquid phase impregnation and deposition: Add all the hard carbon matrix obtained in S1 (about 4.8g) to the solution prepared in S2, and impregnate continuously with stirring in a 50°C water bath for 2 hours.
[0039] Step 4, Separation and Drying: The suspension obtained in S3 was filtered, the solid part was washed with a small amount of ethanol, and then dried at 80°C for 6 hours to obtain a hard carbon intermediate coated with glucose precursor.
[0040] Step 5, Low-Temperature Heat Treatment: The intermediate obtained from S4 is placed in a tube furnace and heated to 300°C at a heating rate of 2°C / min under an argon atmosphere, and then kept at this temperature for 3 hours. During this process, the glucose on the surface undergoes dehydration, cross-linking, and partial carbonization.
[0041] Step 6: Cooling: After the heat treatment is completed, stop heating and allow it to cool naturally to room temperature under an argon atmosphere.
[0042] Step 7, Post-processing: The cooled material is lightly ground and passed through a 400-mesh sieve to obtain the final surface-modified hard carbon material A. The thickness of the surface-modified layer was measured to be approximately 5-8 nm by TEM characterization.
[0043] Example 2: Step 1, Pretreatment: Clean 5g of hard carbon powder with anhydrous ethanol using ultrasonic cleaning for 30 minutes, filter, and then dry under vacuum at 80℃.
[0044] Step 2: Prepare the coating precursor solution: Weigh 3g of phenolic resin (polymer source) and 0.2g of ferric nitrate (catalyst), dissolve them in 47g of ethanol, and stir until completely dissolved.
[0045] Step 3, Liquid phase impregnation and deposition: Add the hard carbon matrix obtained in S1 to the above solution and impregnate at room temperature for 1 hour with stirring.
[0046] Step 4, Separation and Drying: Centrifuge separation, and vacuum drying of the solid at 60℃.
[0047] Step 5: Low-temperature heat treatment: Under nitrogen protection, the temperature is increased to 250℃ at a rate of 3℃ / min and held at that temperature for 4 hours.
[0048] Step 6: Cooling: Nitrogen gas is used to lower the temperature.
[0049] Step 7, Post-processing: Grind and pass through a 300-mesh sieve to obtain surface-modified hard carbon material B.
[0050] Example 3: Similar to the steps in Example 1, except that: In the second step, 2g of polyvinyl alcohol and 0.1g of boric acid were used as precursors.
[0051] In the fifth step, the heat treatment conditions are: heating to 180°C at a rate of 1°C / min under argon atmosphere, and holding at that temperature for 5 hours.
[0052] Surface-modified hard carbon material C was obtained.
[0053] Comparative example: Unmodified commercial hard carbon material, designated D.
[0054] Electrochemical performance testing: Materials A, B, and C obtained in Examples 1-3, and comparative material D, were used as active materials. They were mixed with conductive carbon black and a binder (sodium carboxymethyl cellulose and styrene-butadiene rubber) at a mass ratio of 8:1:1 to form a slurry. This slurry was coated onto copper foil, and after drying, rolling, and stamping, a negative electrode sheet was formed. Using metallic sodium as the counter electrode and 1M NaClO4 in EC / PC (1:1 vol%) with 5% FEC as the electrolyte, a CR2032 coin cell was assembled in an argon-filled glove box.
[0055] Table 1: Comparison of electrochemical performance between modified hard carbon materials (A, B, C) and unmodified material (D)
[0056] The above data collectively demonstrate that the surface-modified hard carbon materials prepared using different embodiments (A, B, C) of this invention outperform the unmodified commercial hard carbon materials (D) in key indicators such as first-efficiency performance, cycle life, and rate performance. This verifies that the surface modification method provided by this invention has good universality and reproducibility, can effectively construct a functionalized interface layer, simultaneously improve the comprehensive electrochemical performance of the hard carbon anode, and solve the core problems of performance imbalance and interface instability mentioned in the background art.
[0057] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for surface modification of hard carbon material for sodium-ion battery negative electrodes, characterized in that, Includes the following steps: S1. Pretreatment: The hard carbon raw material is pretreated to obtain a clean hard carbon matrix; S2. Preparation of precursor solution: Prepare a coated precursor solution containing a carbon source or polymer source and a catalyst. S3. Impregnation and deposition: The clean hard carbon matrix obtained in step S1 is dispersed in the coating precursor solution prepared in step S2, and liquid phase impregnation and deposition are performed to make the precursor uniformly adhere to the surface of the hard carbon matrix. S4. Separation and drying: The hard carbon matrix with the precursor attached to its surface obtained in step S3 is separated and dried to obtain a hard carbon intermediate coated with the precursor. S5. Low-temperature heat treatment: Under a protective atmosphere, the hard carbon intermediate coated with the precursor obtained in step S4 is subjected to low-temperature heat treatment at a temperature of [temperature value missing]. ,in The heat treatment time is , where 1h≤ ≤6h, allowing the surface-attached precursors to undergo cross-linking, curing, or partial carbonization, forming a uniform, dense, and firmly bonded organic-inorganic composite modified layer on the surface of the hard carbon matrix; S6. Cooling: The hard carbon matrix after heat treatment in step S5 is naturally cooled to 20℃-30℃ to obtain the surface-modified hard carbon material. S7. Post-processing: The surface-modified hard carbon material obtained in step S6 is post-processed, including grinding and sieving, to obtain the final product.
2. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 1, characterized in that, The specific preprocessing steps in step S1 are as follows: S11. Pickling treatment: Immerse the hard carbon raw material in an acidic solution at a temperature... Lower stirring processing time To remove surface impurities and some unstable oxygen-containing functional groups, among which , ; S12. Washing treatment: The acid-washed hard carbon raw material is repeatedly washed with deionized water until the pH value of the washing solution reaches 6-8. S13. Drying treatment: Place the washed hard carbon raw material in a dry environment at a temperature... Next drying time A clean hard carbon matrix is obtained, in which... , .
3. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 1, characterized in that, The specific steps for preparing the precursor solution in step S2 are as follows: S21. Raw material selection and weighing: Select a carbon source or polymer source. and catalysts And weigh them precisely; S22, Solvent Dissolution: Dissolve the weighed carbon source or polymer source in solvent. and catalysts Add solvent middle; S23. Stirring and homogenizing: at temperature Continue stirring time The process continues until the solute is completely dissolved and a homogeneous and stable solution is formed, thus obtaining the coated precursor solution. , .
4. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 3, characterized in that, The carbon source or polymer source is selected from at least one of glucose, sucrose, phenolic resin, polyvinyl alcohol, polypyrrole, and polyaniline; the catalyst is an acidic catalyst or a metal salt catalyst; and the solvent... The solvent is water, ethanol, acetone, or a mixture thereof, and the coating precursor solution contains a carbon source or a polymer source. mass concentration is ,catalyst mass concentration is And satisfy , .
5. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 4, characterized in that, The specific steps for impregnation deposition in step S3 are as follows: S31. Dispersion and mixing: The clean hard carbon matrix obtained in step S1 is added to the coating precursor solution prepared in step S2, and mechanical stirring or ultrasonic dispersion is performed to form a uniform suspension system. S32. Constant Temperature Impregnation: The suspension system is placed in a constant temperature environment, and impregnation is performed at a constant temperature. Subsequent immersion time And ensure that the hard carbon matrix is in full contact with the precursor solution, wherein , ; S33. Deposition complete: After impregnation, the precursor is uniformly attached to the surface of the hard carbon matrix through physical adsorption and / or chemical action, resulting in a hard carbon matrix with the precursor attached to its surface.
6. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 5, characterized in that, In step S33, the mass ratio of the hard carbon matrix to the solute in the coated precursor solution... satisfy The solute in the coated precursor solution is a carbon source or a polymer source and a catalyst.
7. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 5, characterized in that, The specific steps for separation and drying in step S4 are as follows: S41. Solid-liquid separation: The hard carbon matrix with the precursor attached to its surface obtained in step S33 is separated from the remaining coated precursor solution. The separation method is filtration or centrifugation. S42. Cleaning and Pre-drying: Use a small amount of the solvent described above. The separated solid material is rinsed to remove excess solute physically adsorbed on the surface, followed by temperature... The following steps are performed to initially dry the residue and remove any residual solvent. ; S43. Deep Drying: Place the pre-dried solid material in a drying oven under vacuum or inert atmosphere protection, and dry it at a temperature... Deep drying time A thoroughly dried hard carbon intermediate with uniform precursor coating was obtained, wherein... , .
8. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 7, characterized in that, The specific steps for the low-temperature heat treatment in step S5 are as follows: S51. Atmosphere protection and charging: The hard carbon intermediate with uniform precursor coating obtained in step S43 is placed in a heat treatment furnace, and a protective atmosphere is introduced into the furnace. The protective atmosphere is nitrogen, argon or a mixture thereof. S52, Continuous heating: at the set heating rate The temperature inside the heat treatment furnace is raised from room temperature to the target heat treatment temperature. The heating rate satisfy The target heat treatment temperature satisfy ; S53, Isothermal Reaction: The reaction proceeds at the target heat treatment temperature. Then, maintain this temperature for a constant heating time. ,in This causes the precursors attached to the surface of the hard carbon intermediate to undergo cross-linking, curing, or partial carbonization reactions, thereby forming the organic-inorganic composite modified layer on the surface of the hard carbon matrix.
9. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 8, characterized in that, The specific steps for cooling and temperature reduction in step S6 are as follows: S61. Cooling with the furnace: After completing the constant temperature heat treatment in step S53, stop heating and allow the heat treatment furnace to cool down naturally under the continuous protection of the protective atmosphere. S62. Controlled-rate cooling: Controlling the cooling rate so that the furnace temperature drops from the target heat treatment temperature at a rate not exceeding 10℃ / min. Temperatures dropped below 100°C; S63. Remove the material: After the temperature inside the furnace has cooled naturally to 20℃-30℃, turn off the protective atmosphere and remove the heat-treated hard carbon material to obtain the surface-modified hard carbon material.
10. The method for surface modification of hard carbon material for sodium-ion battery negative electrode according to claim 9, characterized in that, The specific post-processing steps in step S7 are as follows: S71. Preliminary grinding: The surface-modified hard carbon material taken out in step S63 is preliminarily crushed or ground to break up any possible agglomerates. S72. Fine sieving: The ground material is sieved and classified using a standard sieve to select powder that meets the target particle size range. The mesh size of the standard sieve is between 300 and 500 mesh. S73. Packaging and Storage: The sieved final product is packaged and stored in a dry, sealed container for use in the preparation of sodium-ion battery anodes.